Baptizing Harry Potter a Christian reading of J.K. Rowling - Bell, Luke. (Mahwah, N.J. : Hidden Spring, 2010)
The scope and tragedy of the thing : the structure of the series -- More things in heaven and earth : going beyond the normal -- As if a man were author of himself : good against evil -- Be absolute for death : life and death -- Power is made perfect in weakness : power and weakness -- To lay down one's life for one's friends : love and sacrifice -- It is essential that you understand this : freedom and determination -- A pretty boring life : the hidden and the ostentatious -- Telling it like it is : the struggle for truth -- They will see God : purity of heart and purity of blood.
The scope and tragedy of the thing : the structure of the series -- More things in heaven and earth : going beyond the normal -- As if a man were author of himself : good against evil -- Be absolute for death : life and death -- Power is made perfect in weakness : power and weakness -- To lay down one's life for one's friends : love and sacrifice -- It is essential that you understand this : freedom and determination -- A pretty boring life : the hidden and the ostentatious -- Telling it like it is : the struggle for truth -- They will see God : purity of heart and purity of blood.
Includes bibliographical references.
Description based on print version record.
Keywords: Rowling, J. K. -- Religion; Christianity in literature; Children -- Books and reading; Potter, Harry (Fictitious character); LITERARY CRITICISM / European / English, Irish, Scottish, Welsh; Electronic books